2005
DOI: 10.1007/s10162-005-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Interaural Correlation of Single Neurons in the Inferior Colliculusof Guinea Pigs

Abstract: Sensitivity to changes in the interaural correlation of 50-ms bursts of narrowband or broadband noise was measured in single neurons in the inferior colliculus of urethane-anaesthetized guinea pigs. Rate vs. interaural correlation functions (rICFs) were measured using two methods. These methods compensated in different ways for the inherent variance in interaural correlation between tokens with the same expected correlation. The shape of all rICFs could be best described by power functions allowing them to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 37 publications
4
77
1
Order By: Relevance
“…In consequence, the degree of interaural correlation at these frequencies decreases with decreasing SMR. Because binaural neurons can be driven by the stimulus envelope (Batra et al, 1989) and are sensitive to interaural correlation per se (Shackleton et al, 2005), they could pick up these changes.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, the degree of interaural correlation at these frequencies decreases with decreasing SMR. Because binaural neurons can be driven by the stimulus envelope (Batra et al, 1989) and are sensitive to interaural correlation per se (Shackleton et al, 2005), they could pick up these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although ITD sensitivity with low-frequency pure tones in NH improves as frequency is increased from 200 to 500 Hz (Durlach and Colburn 1978), the opposite trend is observed with transposed stimuli-a finding that has also been observed in the responses of neurons in the inferior colliculus of the guinea pig (Griffin et al 2005;Shackleton et al, 2005). In tests of ITD sensitivity to electric pulse trains presented to bilateral CIs, van Hoesel and Tyler (2003) found that performance was worse with pulse rates higher than 200 pps, compared to a rate of 50 pps.…”
Section: High-rate Limitations On Binaural Processingmentioning
confidence: 95%
“…Existing evidence for an upper limit on binaural processing comes both from research with CI listeners, and from experiments in which NH listeners are presented with transposed stimuli (Bernstein and Trahiotis 2002;van der Par and Kohlrausch 1997). Although ITD sensitivity with low-frequency pure tones in NH improves as frequency is increased from 200 to 500 Hz (Durlach and Colburn 1978), the opposite trend is observed with transposed stimuli-a finding that has also been observed in the responses of neurons in the inferior colliculus of the guinea pig (Griffin et al 2005;Shackleton et al, 2005).…”
Section: High-rate Limitations On Binaural Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals where sound localization is critical and available from the neural circuits, it can be used in that way. If not, the general neural architecture still supports adequate sensitivity to sound location, and in addition provides for increased separation of signals from noise and a sensitivity to auditory "spaciousness" through variations in the responses to interaural correlation (Yin et al, 1987;Shackleton et al, 2005;Coffey et al, 2006) In humans using broadband stimuli, there is a gradual increase in thresholds within the physiological range as the sound becomes increasingly lateralized towards the ear. Measurements of this increase range from about a factor of two with clicks (Hafter et al, 1975) up to a factor of about four with noise (Klumpp and Eady, 1957;Mossop and Culling, 1998).…”
Section: Comparison With Neural Thresholdsmentioning
confidence: 99%